2020
DOI: 10.1590/1678-4499.20190309
|View full text |Cite
|
Sign up to set email alerts
|

Silverleaf whitefly-resistant common beans: an investigation of antibiosis and/or antixenosis

Abstract: The silverleaf whitefly Bemisia tabaci biotype B is one of the most important sucking pests of common bean, which causes severe damages and requires frequently synthetic insecticides spraying to protect crop productivity. The use of common bean cultivars resistant to whitefly attack is an important strategy within an integrated pest management (IPM) program. The biological development of B. tabaci confined to 17 bean genotypes was evaluated in greenhouse trials to verify the occurrence of antibiosis. Whitefly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Previous studies have also found resistance of common bean genotypes to other pests (Silva et al 2014, Santos et al 2020b, Shaabani et al 2021, Zimba et al 2022. No-choice tests with Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) Middle East Asia Minor 1 described high levels of antibiosis and/or antixenosis in 'CHIB 06' (Santos et al 2020a). Thus, this landrace genotype is an interesting option for smallholders due to its resistance levels to this sucking insect (whiteflies), an emerging insect vector of phytopathogens to beans in field conditions, as well as the resistance to the bruchid-pest of stored beans.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have also found resistance of common bean genotypes to other pests (Silva et al 2014, Santos et al 2020b, Shaabani et al 2021, Zimba et al 2022. No-choice tests with Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) Middle East Asia Minor 1 described high levels of antibiosis and/or antixenosis in 'CHIB 06' (Santos et al 2020a). Thus, this landrace genotype is an interesting option for smallholders due to its resistance levels to this sucking insect (whiteflies), an emerging insect vector of phytopathogens to beans in field conditions, as well as the resistance to the bruchid-pest of stored beans.…”
Section: Discussionmentioning
confidence: 98%
“…The reduction in the time (days) of development of nymph to adult of B. tabaci in the GCS 07 cultivars can be explained by the fact that insects can decrease the development period in an unfavorable environment, the insect quickly reaches the adult stage, and they may have the chance of survival of the species. Plants with antibiosis characteristics usually prolong the life cycle stages of the insect, causing a high mortality rate (Baldin et al 2017;Horas et al 2018;Latha et al 2018;Santos et al 2020). Studies on the antibiosis resistance factors associated with these materials should be better investigated, characterizing the biochemical composition of these cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…El hecho de que líneas carentes del MM SR2 hayan sobresalido por su mayor rendimiento en condiciones de presión de mosaico amarillo dorado, en comparación con las líneas que poseen este marcador, destaca la importancia de confirmar la resistencia mediante la confrontación con el patógeno, ya que si bien, bgm-1 es el gen más ampliamente usado, el MM SR2, según los estándares actuales, no está estrechamente ligado a este gen (~3-7 cM), lo que resulta en la selección de unas pocas líneas que poseen el marcador, pero que no obstante, son susceptibles al virus, además de que existen otros genes y QTLs cuya acumulación condiciona altos niveles de resistencia a BGYMV (Soler-Garzón et al, 2021), así como otros mecanismos de resistencia al vector, como la antibiosis o antixenosis (Santos et al, 2020), cuya presencia en los materiales evaluados requiere ser estudiada.…”
Section: Genotipounclassified